Principles of Financial and Managerial Accounting - Reeve, James M. (Thomson, 2008)
This book goes beyond presenting theory and procedure with comprehensive, time-tested, end-of-chapter material. Eye openers (formerly discussion questions: contains quick concept review questions and single transaction exercises, which are ideal to help students break down concepts into basic parts, ensuring a solid foundation on which to build. Example exercises: for practice includes two parallel variations of the authors illustrated earlier. Exercises: completely revised and accompanied by a general topic and a reference to chapter objective. Special activities: focus on understanding and solving pertinent business and ethical issues. Comprehensive Problems: located after chapters 4, 5, 10, 14, and 22 to integrate and summarize chapter concepts and test students' comprehension. Financial statement analysis problem: located in chapter 15, this problem features annual report, which allows students to engage current, real world data.